Processed bed elevation picks from airborne radar depth sounding across East and West Antarctica (1966-1987) ... - BEDMAP 1 Consortia (UK Polar Data Centre, Natural Environment Research Council, UK Research & Innovation, 2020)
This is a collection of all vintage BAS radar data that went into BEDMAP 1 (Lythe and Vaughan, 2001) that have not been released so far as line data. BEDMAP data descries the thickness of the Antarctic ice sheet. They have been collected on surveys undertaken over the past 50 years and brought together into a single database. These data have allowed the compilation of a suite of seamless digital topographic models for the Antarctic continent and surrounding ocean. Data are provided as XYZ ASCII line data. ... : RESPAC was the British Antarctic Survey radio-echo sounding database. It included data collected by BAS from 1966 to 1987. A number of different radar systems were used to collect ice thickness and navigation data during these campaigns. All data in RESPAC was incorporated into both the BEDMAP1 (Lythe et al. 2001) and Bedmap2 (Fretwell et al. 2013) compilations. Here we provide basic channels containing information on flight line, data-point location, and ice thickness measurements which are described in the table below. It should be noted that early surveys (prior to 1987) did not use GPS positioning, but were located using a variety of methods such as celestial navigation, inertial avionics (INS), Doppler avionics and dead-reckoning. Furthermore, various processes of "refixing" were applied to most flightlines, with distributed navigational uncertainties through the flight and at fixed points during the flight to the map-position of known landmarks. In summary, all navigational data have large positional ...